The Association Between Family History of Upper Gastrointestinal Cancer and the Risk of Death from Upper Gastrointestinal Cancer–based on Linxian Dysplasia Nutrition Intervention Trial (NIT) Cohort - Sun, Wan-yi; Yang, Huan; Wang, Xiao-kun; Fan, Jin-hu; Qiao, You-lin; Taylor, Philip R. (Frontiers in Oncology, 2022)
Objective: Explore the relationship between family history of upper gastrointestinal (UGI) cancer and mortality risk in patients with a previous cytologic diagnosis of esophageal squamous dysplasia, based on the Linxian Dysplasia Nutrition Intervention Trial (NIT) cohort. Methods: First, we compared subjects of family history with the rest of them to see the risk of family history on death of UGI cancer. Second, we further analyzed the effect of category of relatives, number of relatives with UGI cancer, and diagnosis age of relatives on the UGI death risk. Third, interaction and stratification analyses were done. The COX proportional risk model was used to estimate the hazard ratio (HR) and 95% confidence interval (95%CI). Results: In single factor analysis, family history of UGI cancer increased the risk of death of esophageal squamous cell carcinoma (ESCC) by 27% (HR=1.270, 95%CI1.072-1.504). No associations were observed in gastric cardia carcinoma (GCC) and gastric non-cardia carcinoma (GNCC). After adjusting for multi-factor, a family history of UGI cancer increased 31.9% risk of death from ESCC(HR=1.319,95%CI:1.110-1.567). Subgroup analysis of different types of relatives with UGI cancers, UGI cancers in mother (HR=1.457,95%CI:1.200-1.768), brother (HR=1.522,95%CI:1.117-2.073), and sister (HR=1.999,95%CI:1.419-2.817) were independent risk factors for ESCC death, while father weren’t. In addition, 2 relatives with UGI cancer (HR=1.495, 95%, CI:1.110-2.013) and ≥3 relatives with UGI cancer (HR=2.836, 95%CI:1.842-4.367) significantly increased the risk of ESCC death, and the trend test was statistically significant (P<0.001). Relatives' diagnostic age of 51-60 years (HR=1.322, 95%CI:1.046-1.672) and 41-50 years (HR=1.442, 95%CI:1.078-1.930) were the risk factors for ESCC death, with statistical significance in trend test (P=0.010). No statistically significant result of family history effect on the risk of death from GCC or GNCC was found. Sensitivity analysis of 80% of subjects randomly selected did not change the results. Conclusion: A family history of UGI cancer increases the risk of death from ESCC, but not from GCC or GNCC. UGI cancer in mother may raise the risk of death from ESCC, but not father. Further studies are needed to explore the mechanisms associated with family history of UGI cancer and the risk of death.